Using zero inflated models to analyze dental caries with many zeroes - Javali Shivalingappa; Pandit Parameshwar (Wolters Kluwer Medknow Publications, 2010)
Aim: The study aimed to analyze and determine the factors associated with dental caries experience contains many zeros by zero inflated models. Design: A cross sectional design was employed using clinical examination and questionnaire with interview method. Materials and Methods: A study was conducted during March-August 2007 in Dharwad, Karnataka, India, involved a systematic random samples of 1760 individuals aged 18-40 years. The dental caries examination was carried out by using DMFT index (i.e. Decayed (D), Missing (M), Filled (F)). The DMFT index data contains many zeros were analyzed with Zero Inflated Poisson (ZIP) and Zero Inflated Negative Binomial (ZINB) models. Results: The study findings indicated, the variables such as family size, frequency of brushing and duration of change of toothbrush were positively associated with dental caries. But the variable the frequency of sweet consumption is negatively associated with dental caries experience in Zero Inflated Poisson (ZIP) and Zero Inflated Negative Binomial (ZINB) models. Conclusions: The ZIP model is a very good fit over the standard Poisson model and the ZINB is the better statistical fit compared to the Negative Binomial model. The Zero Inflated Negative Binomial model is better fit over the Zero Inflated Poisson model for modeling the DMF count data.